Vitamin D deficiency is a potential risk factor for lipid Amphotericin B nephrotoxicity. - Daniela Ferreira; Ana Carolina de Bragança; Rildo Aparecido Volpini; Maria Heloisa Massola Shimizu; Pedro Henrique França Gois; Adriana Castello Costa Girardi; Antonio Carlos Seguro; Daniele Canale (Public Library of Science (PLoS), 2019)
Invasive fungal infections (IFI) is a worldwide serious health problem and Amphotericin B (AmB) has been considered the drug of choice for IFI treatment. Despite its efficacy, clinical use of AmB has been associated with renal toxicity. Some lines of evidence have shown that an extemporaneous lipid emulsion preparation of AmB (AmB/LE) was able to attenuate nephrotoxicity, presenting similar benefits at a lower cost. Studies have been demonstrating that hypovitaminosis D may hasten the progression of kidney disease and reflect on a worse prognosis in cases of drug-induced nephrotoxicity. In view of the high worldwide incidence of hypovitaminosis D, the aim of this study was to investigate whether vitamin D deficiency may induce AmB/LE-related nephrotoxicity. Wistar rats were divided into four groups: control, received a standard diet for 34 days; AmB/LE, received a standard diet for 34 days and AmB/LE (5 mg/kg/day) intraperitoneally in the last 4 days; VDD, received a vitamin D-free diet for 34 days; and VDD+AmB/LE, received a vitamin D-free diet for 34 days and AmB/LE as described. At the end of the protocol, animals were euthanized and blood, urine and renal tissue samples were collected in order to evaluate AmB/LE effects on renal function and morphology. Association of AmB/LE and vitamin D deficiency led to diminished glomerular filtration rate and increased tubular injury, evidenced by reduced renal protein expression of NaPi-IIa and TRPM6 leading to hyperphosphaturia / hypermagnesuria. VDD+AmB/LE rats also presented alterations in the PTH-Klotho-FGF-23 signaling axis, urinary concentrating defect and hypertension, probably due to an inappropriate activation of the renin-angiotensin-aldosterone system. Hence, it is important to monitor vitamin D levels in AmB/LE treated patients, since vitamin D deficiency induces AmB/LE nephrotoxicity.